Intercellular Conduction Optimizes Arterial Network Function and Conserves Blood Flow Homeostasis During Cerebrovascular Challenges. Issue 3 (March 2020) - Zechariah, Anil; Tran, Cam Ha T.; Hald, Bjorn O.; Sandow, Shaun L.; Sancho, Maria; Kim, Michelle Sun Mi; Fabris, Sergio; Tuor, Ursula I.; Gordon, Grant R.J.; Welsh, Donald G.
Abstract : Objective: Cerebral arterial networks match blood flow delivery with neural activity. Neurovascular response begins with a stimulus and a focal change in vessel diameter, which by themselves is inconsequential to blood flow magnitude, until they spread and alter the contractile status of neighboring arterial segments. We sought to define the mechanisms underlying integrated vascular behavior and considered the role of intercellular electrical signaling in this phenomenon. Approach and Results: Electron microscopic and histochemical analysis revealed the structural coupling of cerebrovascular cells and the expression of gap junctional subunits at the cell interfaces, enabling intercellular signaling among vascular cells. Indeed, robust vasomotor conduction was detected in human and mice cerebral arteries after focal vessel stimulation: a response attributed to endothelial gap junctional communication, as its genetic alteration attenuated this behavior. Conducted responses were observed to ascend from the penetrating arterioles, influencing the contractile status of cortical surface vessels, in a simulated model of cerebral arterial network. Ascending responses recognized in vivo after whisker stimulation were significantly attenuated in mice with altered endothelial gap junctional signaling confirming that gap junctional communication drives integrated vessel responses. The diminishment in vascular communication also impaired the critical ability of the cerebral vasculature to maintain blood flow homeostasis and hence tissue viability after stroke. Conclusions: Our findings highlight the integral role of intercellular electrical signaling in transcribing focal stimuli into coordinated changes in cerebrovascular contractile activity and expose, a hitherto unknown mechanism for flow regulation after stroke. Abstract : Supplemental Digital Content is available in the text.